농업부문 워크아웃 도입방향 - 박성재 (한국농촌경제연구원, 2003)
A Study on a Workout Program for Farm Households in Korea It was reported that the debt of a farm household decreased 2.3 percent in the previous year, which was the first time since 1972. Farm household debts had steadily increased severly threatening the stability of farm household economy. As a response, the government established a measure to solve the debt problem in 1998, when the shock of currency crisis severly affected the agricultural sector. Main contents of the measure include policy loans repayment schedule for two years, interest rates reduction, and special mid-term loans provision for farms suffering from the heavy burden of debts and liquidity pressure. However, most farmers did not appreciate the measure as a proper and sufficient program to alleviate difficulty of farm household economy. Thus, the government increased the amount of special mid-term loans and added new measures such as replacing the privately guaranteed loans with the publicly guaranteed loans in 1999 and 2000. Especially, the national assembly passed the Special Act of Lessening Farm and Fishery Household Debts at the end of 2000. Under the special act the repayment of policy loans was allowed to be postponed by 5 years including 2 year grace period, and the special mid-term loans worth 3.1 trillion won were newly provided. The Mutual Credit Loans, the cooperative loans with higher interest rates compared with policy loans, were replaced with lower interest rate loans. The government provided concessionary loans with 5 percent interest per year for the victims of consignment to pay off for their neighbors' borrowings. An incentive refunding 20 percent of interest paid was introduced to encourage voluntary repayments rather than postponement of policy loans pay off. Most farmers having policy loans or agricultural cooperative loans were entitled to the measures of farm household debts. But the farmers having a lot of financial assets, houses in urban areas, or a luxurious car, couldn't be the beneficiaries because they were thought as rich and financially sound enough. However, farm household economy has still stagnated since 1997, and the market interest rates have steadily declined from 10 percent level to 6 percent level. Furthermore, all of ruling and opposition parties announced that they would solve the debt problem if they capture the power during the presidential election in 2002, which pressed the government to revise the debt measures. Thus, the government and the national assembly tried to amend the act of farm household debts in 2003. The debt measures since 1987 have supported most farmer borrowers. However, there were little screening processes for borrowers. This led to severe moral hazard and distortion of income distribution. Furthermore, the fragile farm households under heavy debt burden could not be supported sufficiently by the measures because of budget constraints, while the farms with sound financial conditions and no need of support also could get benefits from the debt measures. Thus the measures have been criticized as policy failures. Although the Korea government often used these kinds of debt measures since 1987, there has been no action program to support fragile farms in the sense of financial structure. The agricultural cooperatives are the most important financial institutions and dominate rural financial markets as an almost monopoly institution, but they do not provide independent financial services to reconstruct fragile farms such as debt restructuring or reduction of debt burden. Most farm households could easily fall into the trap of financial failure when external shocks such as natural disasters or abrupt price drop hit them. If a farm becomes delinquent and in arrear with payment, the interest rates of past due debts rise sharply so that it is getting more hard for the farm to repay the debts, pushing the farm to be bankrupt. Mindful of the current situation, this study suggests a workout program for farm households as an alternative to the debt measure. The paper criticizes the existing debt measures as policy failures because they have distorted income distribution, caused moral hazard, and been ineffective. We designed a workout program and a program of land liquidation for farm restructuring. The workout program consists of an executing committee, fund to support the program, and financial institutions. The executing committee makes rules and criteria for screening farm households that are entitled to the workout program, designs the financial restructuring programs, and monitors overall process of the workout program. Any financial institutions related to agricultural sector can participate in the executing committee and the workout program related to the loans it provided. The committee identifies the farm households qualifying for the workout program and suggests a proper reconstruction program for both lenders and borrowers. If the lenders agree to the suggested program, the workout will start for the borrowers. Basically this system is similar to the individual workout program operating by the Credit Counseling and Recovery Services, but is different from it in terms of dealing with the policy loans in the agricultural sector. It is not desirable for the government to directly manage the workout program of policy loans. In rural areas, the counseling service committee for the farm household debts can work to choose the entitled and evaluate the workout program. The committee will cover several counties and some members of the committee will be chosen among the persons not related to and acquaintant with the areas. Qualified farmers can be applied with the workout program by the primary agricultural cooperatives in the area, or the financial institutions, and the local governments can recommend farmers for program application. The fund for workout program can be contributed by the central government, local governments, and financial institutions, which are related to the revitalization of farm households. Especially, it is important for the local governments to join this program since they are responsible for supporting their residents and have a wealth of information about the farm households. It is desirable for the central government to support local governments by providing the workout funds through subsidies, because some local governments are financially poor. The workout program will be designed and operated as diverse supporting schemes such as lowering interest rates, postponing repayment schedules, replacing the loans with concessionary interest rate loans, or making other financial restructuring programs. For the farm households with too many debts, it needs to conduct financial restructuring rather than debt restructuring, so that the high debt ratio (debt/assets) should be reduced through asset sales. It is important to encourage the borrowers to overcome debt issues and to implement restructuring works. The workout committee should sign an MOU with the borrowers but terminate it when the borrowers do not keep their words. If a farm size decreases because of asset sales, the farm household could face problems in generating income and revitalizing its economy. Thus, it needs for the farm to cultivate the farm land it sold via leasing. This idea is workable when a public institution buys and leases the land if the farmer wants. That is, the farmer should pay interests of debts before selling the land but pay rents of the land after the land sales. The key idea is that in Korea, rents of farm land are cheaper than interests of loans, so it may be feasible. However, the land market should be flexible and kept in a stable condition. If land price will drop continuously for the long period, this idea will not be realized. There are some farmers who are not able to repay their debts in the long run but suffering from financial and psychological stress. For them, it is desirable to write off debts after selling their farm land, if they want. In that case, the government may provide job training and moving costs. At present, many bankrupt farmers are leaving their home town without any safety net and hope. Researchers: Park Seong-Jae, Hwang Eu-Sik, Kim Tae-Gon Email address: seongjae@krei.re.kr
Keywords: 농업부문; 워크아웃